Consumer Protection on Nonofficial Drugs Case in Indonesia: How Far the Legal Protection is? - Sari, Chatrin Intan (Law Research Review Quarterly, 2021)
The purpose of this study is to know how the legal protection for consumers on the circulation of nonofficial drugs, and how the accountability of business actors on the circulation of nonofficial drugs. The method used in this research is the normative legal approach. This research found that legal protection to consumers on the circulation of illegal drugs conducted by the government through the Agency of Drugs and Food (BPOM). The BPOM shows the attention that the government has run its supervision. In addition, the protection of consumer law arising from the existence of rights and obligations set forth in Article 4 letters a and c, article 7 letters a and d, article 8 paragraph 1 letter a, d and e of Law Number 8 of 1999 concerning Consumer Protection. The fulfillment of consumer rights over security, the right to be heard, the correct, clear, and honest information regulated in the Law is still not fulfilled. Article 98 paragraph 2, Article 106 paragraph 1 and 2 of Law Number 36 of2009 on Health. It is also found that the business actor is responsible as the manufacturer of the goods because the importer of the goods is not an agent or official importer. The business actor who is an individual shall be liable for the losses incurred even if only as an importer not as a producer of the goods.